Discovery of selective, antimetastatic and anti-cancer stem cell metallohelices via post-assembly modification. Issue 37 (7th August 2019) - Song, Hualong; Rogers, Nicola J.; Allison, Simon J.; Brabec, Viktor; Bridgewater, Hannah; Kostrhunova, Hana; Markova, Lenka; Phillips, Roger M.; Pinder, Emma C.; Shepherd, Samantha L.; Young, Lawrence S.; Zajac, Juraj; et al.
Abstract : A remarkable array of mechanistic and pharmacological behaviours is discovered via click derivatisation of asymmetric, optically pure helicate-like compounds. Abstract : Helicates and related metallofoldamers, synthesised by dynamic self-assembly, represent an area of chemical space inaccessible by traditional organic synthesis, and yet with potential for discovery of new classes of drug. Here we report that water-soluble, optically pure Fe(ii )- and even Zn(ii )-based triplex metallohelices are an excellent platform for post-assembly click reactions. By these means, the in vitro anticancer activity and most importantly the selectivity of a triplex metallohelix Fe(ii ) system are dramatically improved. For one compound, a remarkable array of mechanistic and pharmacological behaviours is discovered: inhibition of Na + /K + ATPase with potency comparable to the drug ouabain, antimetastatic properties (including inhibition of cell migration, re-adhesion and invasion), cancer stem cell targeting, and finally colonosphere inhibition competitive with the drug salinomycin.